Prognostic model for patients with traumatic brain injuries and abnormal computed tomography scans. (August 2017) - Junior, Jefferson Rosi; Welling, Leonardo C.; Schafranski, Marcelo; Yeng, Lin Tchia; do Prado, Rogério Ruscito; Koterba, Edwin; de Andrade, Almir Ferreira; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha
Highlights: Bedside estimation of prognosis is a challenge. The authors developed a prognostic model for assessment of survival chances. This model is to be applied before in-hospital therapeutic interventions. Abstract: Traumatic brain injury (TBI) is an important cause of death and disability worldwide. The prognosis evaluation is a challenge when many variables are involved. The authors aimed to develop prognostic model for assessment of survival chances after TBI based on admission characteristics, including extracranial injuries, which would allow application of the model before in-hospital therapeutic interventions. A cohort study evaluated 1275 patients with TBI and abnormal CT scans upon admission to the emergency unit of Hospital das Clinicas of University of Sao Paulo and analyzed the final outcome on mortality. A logistic regression analysis was undertaken to determine the adjusted weigh of each independent variable in the outcome. Four variables were found to be significant in the model: age (years), Glasgow Coma Scale (3–15), Marshall Scale (MS, stratified into 2, 3 or 4, 5, 6; according to the best group positive predictive value) and anysochoria (yes/no). The following formula is in a logistic model ( USP index to head injury ) estimates the probability of death of patients according to characteristics that influence on mortality. We consider that our mathematical probability model ( USP Index ) may be applied to clinical prognosis in patients with abnormal CT scans after severe traumatic brain injury.